Foreign direct investment spillovers in Portugal : additional lessons from a country study - Júnior, Renato G. Flôres (2022)
This paper investigates the impact of FDI on the productivity of Portuguese manufacturing sectors. Model specification is improved by considering the choice of the most appropriate interval of the technological gap for spillovers diffusion. We also allow for sectoral variation in the coefficients of the spillover effect; idiosyncratic sectoral factors are identified by means of a fixed effects model. Inter-sectoral positive spillover effects are examined. Significant spillovers require a proper technological differential between foreign and domestic producers and favourable sectoral characteristics. They may occur in modern industries in which the foreign firms have a clear, but not too sharp, edge on the domestic ones. Agglomeration effects are also one pertinent specific influence.